2020
DOI: 10.3389/fgene.2020.00805
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic lncRNA, miRNA, and mRNA Signatures in Papillary Thyroid Carcinoma

Abstract: The current focus in the treatment of papillary thyroid carcinoma (PTC) is tumor progression. The aim of this study was to build RNA-based classifiers and develop a comprehensive model to provide progression-free interval (PFI) risk prediction for PTC. The RNAseq data, miRNAseq data, and clinical information of PTC were downloaded from The Cancer Genome Atlas database. Based on the differently expressed RNAs, the least absolute shrinkage and selection operator (LASSO) Cox regression model was utilized to build… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Considerable efforts have been made in genomics, epigenomics, and proteomics analysis to elucidate the mechanisms of TC occurrence and progression [27][28][29]. Studies have shown changes in non-coding RNAs (ncRNAs) at expression level, including microRNAs and long non-coding RNAs (lncRNAs), in papillary TC [30][31][32]. This study aimed mainly to investigate the biological function and molecular mechanism of microRNA-196a-5p in TC, with the hope of providing new targets for TC.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable efforts have been made in genomics, epigenomics, and proteomics analysis to elucidate the mechanisms of TC occurrence and progression [27][28][29]. Studies have shown changes in non-coding RNAs (ncRNAs) at expression level, including microRNAs and long non-coding RNAs (lncRNAs), in papillary TC [30][31][32]. This study aimed mainly to investigate the biological function and molecular mechanism of microRNA-196a-5p in TC, with the hope of providing new targets for TC.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many survival prediction models have been developed to identify prognostic biomarkers. Researchers usually use Kaplan–Meier and time-dependent ROC curves to measure predictive performance ( 30 , 31 ). However, these studies are only based on the probabilities calculated using a single prediction model, which lacks discernibility in long-term survival.…”
Section: Discussionmentioning
confidence: 99%
“…Differently expressed miRNAs were reported to predict the progression-free interval in papillary thyroid carcinoma, suggesting its prognostic role in papillary thyroid carcinoma. 21 Moreover, differently expressed miRNAs were related to different risks of recurrence and histological types in papillary thyroid carcinoma, suggesting that miRNAs might be potential therapeutic targets for treatment of papillary thyroid carcinoma. 22 Studies have shown the tumor suppressive role of miR-671-5p in various tumors.…”
Section: Discussionmentioning
confidence: 99%